2010
DOI: 10.1063/1.3498676
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strained island growth at step-edges on GaAs(110)

Abstract: Selective epitaxial growth of GaAs on Si with strained short-period superlattices by molecular beam epitaxy under atomic hydrogen irradiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…27 This principle has enabled us to demonstrate high-quality tensile GaAs/InAlAs and GaP/GaAs nanostructures on both (110) and (111) surfaces. 9,21,[28][29][30] Since tensile strain can strongly reduce semiconductor bandgaps, 9,30 tensile QDs on these surfaces are promising for optoelectronic devices operating at long wavelengths. Moreover, tensile GaAs/InAlAs QDs grown on (111) surfaces are perfectly suited to entangled photon generation due to their high electronic symmetry.…”
Section: Tensile Quantum Dotsmentioning
confidence: 99%
“…27 This principle has enabled us to demonstrate high-quality tensile GaAs/InAlAs and GaP/GaAs nanostructures on both (110) and (111) surfaces. 9,21,[28][29][30] Since tensile strain can strongly reduce semiconductor bandgaps, 9,30 tensile QDs on these surfaces are promising for optoelectronic devices operating at long wavelengths. Moreover, tensile GaAs/InAlAs QDs grown on (111) surfaces are perfectly suited to entangled photon generation due to their high electronic symmetry.…”
Section: Tensile Quantum Dotsmentioning
confidence: 99%
“…6,[28][29][30] We then deposited GaP onto the smooth GaAs(110) buffers to test our hypothesis that dislocation-free self-assembly would occur. 21 Due to its smaller lattice constant, GaP on GaAs experiences 3.7% tensile strain. We found that this tensile-strain causes the GaP to self-assemble into QDs ( Fig.…”
Section: Gap Qds On Gaas(110)mentioning
confidence: 99%
“…To this end, we have pioneered a new, single-step approach based on molecular beam epitaxy (MBE) that enables the selfassembly of dislocation-free, tensile-strained QDs on (111) and (110) surfaces. 5,[21][22][23][24][25] The success of this approach comes from recognizing that combining tensile strain and a (111) or (110) surface restores the energy barrier to dislocation nucleation and glide. On both the (111) and (110) surfaces, the tensile strain-induced shear stresses align with the respective {111} glide planes to effectively reproduce the situation for compressive strain on a (100) surface.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Studies on (In,Ga)(As,P) heteroepitaxial strained films (thick layers and QWs) evidence the presence of composition modulations depending on the strain state (tensile vs. compressive) of the layer. In this material system, stronger composition fluctuations were observed for tensile strained layers, compared with compressively strained ones.…”
mentioning
confidence: 98%